The Effect of Ratio Starfruit Pulp with Lime Juice and Pectin Concentration on the Quality of Starfruit Slice Jam - Efanny Dinny Simarmata; Ismed Suhaidi; Era Yusraini (Jurnal Rekayasa Pangan dan Pertanian, 2016)
This research was aimed to know the effect of ratio of  starfruit pulp with lime juice and pectin concentration on the quality of starfruit slice jam. This research was conducted using a completely randomized design with two factors, namely the ratio of starfruit pulp with lime juice (95% : 5%, 90% : 10%, 85% : 15%, 80% : 20%) and pectin concentration (P) (0,75%, 1,00%, 1,25%, dan 1,50%). The parameters analyzed were the level of moisture content, total soluble solid, vitamin C content, pH value, crude fiber content, crude pectin content, score of color, texture, hedonic flavor and taste. The results showed that the ratio of strafruit pulp with lime juice showed highly significant effect (P<0,01) on total soluble solid, vitamin C content, pH value, crude fiber content, crude pectin content; had significant effect (P<0,05) of hedonic taste and had no effect (P>0,05) on the level of moisture content, score of color, texture, and hedonic flavor. The pectin concentration had highly significant effect (P<0,01) on moisture content, total soluble solid, pH value, crude fiber content, crude pectin content, score of color, texture and had no effect (P>0,05) on vitamin C content, hedonic of flavor and taste. The interaction starfruit pulp with lime juice and pectin concentration showed had highly significant effect (P<0,01) on crude pectin content, hedonic taste but had no effect (P>0,05) on moisture content, total soluble solid, vitamin C content, pH value, crude fiber content, score of color, texure  and hedonic of flavor. Combination of starfruit pulp with lime juice of 95%:5% and pectin concentration of 0,75% produced the best quality of slice jam. Keywords : lime juice, pectin, slice jam, starfruit